156k views
4 votes
What is the inverse of the function f(x) = 2x + 1?

1
1
h(x) =
X-
2
2
1
1
Oh(x) =
- x +
O h(x) =
3x-2
Oh(x) =
= {x+2
Mark this and return
Save and Exit
Next
Submit

2 Answers

4 votes

Answer:


\displaystyle f^(-1)(x)= (1)/(2)x - (1)/(2)

Explanation:

f(x) = 2x + 1

f(x) = y (output)

y = 2x + 1

Solve for x.

y - 1 = 2x

Divide 2 on both sides.

y/2 - 1/2 = x

1/2y - 1/2 = x

Switch variables.

1/2x - 1/2 = y


f^(-1)(x)= (1)/(2)x - (1)/(2)

User Mufri A
by
6.0k points
5 votes

Answer:


f^(-1) = (x-1)/(2)

Explanation:


f(x) = 2x+1

Replace it with y


y = 2x+1

Exchange the values of x and y


x = 2y+1

Solve for y


x = 2y+1

Subtracting 1 from both sides


2y = x-1

Dividing both sides by 2


y = (x-1)/(2)

Replace it by
f^(-1)

So,


f^(-1) = (x-1)/(2)

User Art Shendrik
by
5.7k points